PENGARUH SERTIFIKASI HALAL DAN HARGA TERHADAP KEPITUSAN PEMBELIAN (STUDI KASUS PADA ICE CREAM MIXUE CICERI KOTA SERANG) - Reza Syah Fahlefi; Henny Saraswati; Budi Sudrajat; Wahyu Hidayat; Mutamimah, Fadhilatul; Mat’atul Ainiyah (Moneta: Jurnal Manajemen & Keuangan Syariah, 2023)
This study examines the impact of pricing and halal certification on purchasing decisions using the case study of Ice Cream Mixue Ciceri Serang. The study's population consisted of 40 individuals, all genders, between the ages of 15 and 30, who had purchased ice cream mixue. Data was acquired by distributing questionnaires to 40 respondents. According to study, shoppers' decisions about Ice Cream Mixue Ciceri Serang have a positive and considerable impact on price and halal certification.